2014
DOI: 10.1371/journal.pone.0106728
|View full text |Cite
|
Sign up to set email alerts
|

Bone Disease in Newly Diagnosed Lupus Nephritis Patients

Abstract: IntroductionBone loss in Lupus Nephritis (LN) patients is common and multifactorial. The aim of this study was to evaluate the bone status of newly diagnosed LN patients and their correlation with inflammatory factors involved in LN physiopathology.MethodsWe studied 15 pre-menopausal patients with ≤2 months of diagnosed SLE and LN. Patients with prior kidney or bone disease were excluded. In addition to biochemical evaluation (including 25-hydroxyvitamin D3 [25(OH)D] and Monocyte Chemotactic Protein (MCP1) dos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 88 publications
0
2
0
1
Order By: Relevance
“…59 In a prospective cohort study of 653 SLE patients, significantly higher levels of serum TNF-a were seen in SLE patients compared to non-autoimmune controls. 60 In addition, a significant inverse correlation between serum 25(OH)D and TNF-a levels was observed in patients with lupus nephritis, 61 suggesting that vitamin D deficiency may possibly be linked to elevated TNF-a levels in SLE patients.…”
Section: Possible Mechanisms By Which Vitamin D Deficiency Leads To Fmentioning
confidence: 99%
“…59 In a prospective cohort study of 653 SLE patients, significantly higher levels of serum TNF-a were seen in SLE patients compared to non-autoimmune controls. 60 In addition, a significant inverse correlation between serum 25(OH)D and TNF-a levels was observed in patients with lupus nephritis, 61 suggesting that vitamin D deficiency may possibly be linked to elevated TNF-a levels in SLE patients.…”
Section: Possible Mechanisms By Which Vitamin D Deficiency Leads To Fmentioning
confidence: 99%
“…Other studies have shown the relationship of SLE nephritis with bone mass loss apparently without the influence of glucocorticoid use. 35,36 One study with 15 newly diagnosed lupus nephritis (≤2 months) patients within a mean of 34-day glucocorticoid initiation therapy showed that these patients presented with significantly reduced osteoid volume, osteoid thickness, osteoid surface, mineralization surface and bone formation rate on bone biopsy, associated with an increased eroded surface and osteoclast surface. 35 Although these patients had been exposed to glucocorticoid use, this study showed a higher expression of monocyte chemotactic protein in bone tissue of lupus nephritic patients that is associated with renal disease activity.…”
Section: Discussionmentioning
confidence: 99%
“…Portanto, sumariamente, osteoblastos cultivados em um microambiente com elevados níveis de TNF-, IL-6 e talvez IL-2, como nossas culturas de hFOB 1.19, poderia induzir a produção de RANKL, suportando nosso achado de mRNA de RANKL elevado, e poderia também inibir a expressão de OPG, substanciando nossa detecção de menor nível da proteína OPG na scélulas NL. Tomados conjuntamente, esses achados podem suportar as alterações ósseas detectadas em biópsia de pacientes com diagnóstico recente de nefrite lúpica 42 .…”
Section: Rankl/opgunclassified